The Acquired Immunodeficiency Syndrome: current status. - Quagliarello, V. (Yale Journal of Biology and Medicine, 1982)
A recently recognized syndrome of acquired immunodeficiency (Acquired Immunodeficiency Syndrome-AIDS) has arisen since June 1981. It has received international attention. The clinical spectrum consists of repeated opportunistic infections, rare malignancies, and autoimmune phenomena, occurring in previously healthy adults with no history of an immunologic disorder. The population subset at risk for this syndrome appears to be predominantly homosexual American males and intravenous drug abusers with rare cases being reported in heterosexuals, hemophiliacs, and foreign patients, especially Haitians. The immunologic aberrancy in all patients described appears limited to T-lymphocyte hyporesponsiveness and imbalance of T-helper and suppressor cells. This disordered immunoregulation is a consistent finding in all reported cases and appears to predispose to the opportunistic infections and malignancies which have been associated with a 40 percent mortality. The underlying factor responsible for the immunoregulatory defect is unknown but possible etiologies include a transmissible infectious agent, drug use, chronic antigen stimulation, and spermatozoa exposure. Treatment of the associated infections and malignancies has been a frustrating endeavor as many patients respond incompletely or relapse soon after successful treatment course. Preventive measures, including patient education, physician awareness, and immunomodulating agents, are discussed.